2022
DOI: 10.1002/humu.24443
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a possible founder synonymous variant in TECTA in multiple individuals with autosomal recessive hearing loss

Abstract: Synonymous variants have been shown to alter the correct splicing of pre-mRNAs and generate disease-causing transcripts. These variants are not an uncommon etiology of genetic disease; however, they are frequently overlooked during genetic testing in the absence of functional and clinical data. Here, we describe the occurrence of a synonymous variant [NM_005422.4 (TECTA):c.327C>T, p.(Gly109=)] in seven individuals with hearing loss from six unrelated families. The variant is not located near exonic/intronic bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In mice, targeted deletion of the TECTA gene results in complete detachment of the TM from the organ of Corti [24]. In humans, nearly all recessive DFNB21 mutations in TECTA result in premature stop codons that may result in either truncated α-tectorin protein products or nonsense-mediated degradation of the TECTA mRNA, and are considered loss-of-function mutations [21].The DFNA8/12 mutations in TECTA, which cause dominant hearing loss, all substitute highly conserved amino acids. The various missense mutations in TECTA that cause DFNA8/12 can be subdivided into classes with a clear genotype/phenotype correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, targeted deletion of the TECTA gene results in complete detachment of the TM from the organ of Corti [24]. In humans, nearly all recessive DFNB21 mutations in TECTA result in premature stop codons that may result in either truncated α-tectorin protein products or nonsense-mediated degradation of the TECTA mRNA, and are considered loss-of-function mutations [21].The DFNA8/12 mutations in TECTA, which cause dominant hearing loss, all substitute highly conserved amino acids. The various missense mutations in TECTA that cause DFNA8/12 can be subdivided into classes with a clear genotype/phenotype correlation.…”
Section: Discussionmentioning
confidence: 99%
“…We revealed that the variant c.5383+6T>A lead to exon 16 skipping in vitro using in vivo RNA analysis at the same time, the results of which are consistent with each other. In previous studies, because of the low levels expressed in TECTA in the blood, total RNA of affected individuals and ethnically matched control individuals were isolated from EBV-transformed lymphoblast [21,22], which is costly and timeconsuming, and the operation is relatively di cult as well. In our study, we used the PAXgene Blood RNA tube to collect RNA of whole blood for protection of RNA stability [23]and undertook further in vivo RNA analysis successfully, which was time-e cient and low-cost and our research protocols can probably be used as reference by other researchers.…”
Section: Discussionmentioning
confidence: 99%